Manajemen keuangan pendidikan: perspektif kajian literatur terhadap efektivitas pengelolaan dana sekolah - Muhammad Redha; Zubaidah; Hayati (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Educational financial management plays a crucial role in enhancing the quality of educational services provided in schools. Effective management of school funds ensures that resources are utilized efficiently, supports the achievement of educational goals, and fosters trust among stakeholders. This research aims to analyze the effectiveness of school fund management through a comprehensive literature review, focusing on key aspects such as transparency, accountability, and good governance. Using a qualitative approach, this study reviews previous research on school fund management and its impact on educational outcomes. The findings indicate that the effectiveness of school fund management is strongly influenced by the managerial competence of school principals, active community involvement, and the consistent application of principles of good governance. Furthermore, accountable and transparent reporting mechanisms are essential in preventing fund misuse, enhancing stakeholder confidence, and promoting sustainable educational development. This study recommends strengthening financial management capacity in schools through regular training, technical assistance, and continuous supervision. The insights gained from this research are expected to provide guidance for policymakers and school administrators to improve the management and utilization of education funds at the school level.